Metagenomic and Metatranscriptomic Analyses Revealed Uncultured Bacteroidales Populations as the Dominant Proteolytic Amino Acid Degraders in Anaerobic Digesters - Mei, Ran; Nobu, Masaru K.; Narihiro, Takashi; Liu, Wen-Tso (Frontiers in Microbiology, 2020)
Current understanding of amino acid (AA) degraders in anaerobic digesters is mainly based on cultured species, whereas microorganisms that play important roles in a complex microbial community remain poorly characterized. This study investigated short-term enrichments degrading single AAs using metagenomics and metatranscriptomics. Metagenomic analysis revealed that populations related to cultured AA degraders had an abundance less than 2.5%. In contrast, metagenomic-assembled bins related to uncultured Bacteroidales collectively accounted for 35% of the community. Phylogenetic analyses suggested that these Bacteroidales populations represented a yet-to-be characterized family, i.e., Bacteroidetes vadinHA17. The bins possessed the genetic capacity related to protein degradation, including surface adhesion (3-7 genes), secreted peptidase (52-77 genes), and polypeptide-specific transporters (2-5 genes). Furthermore, metatranscriptomics revealed that these Bacteroidales populations expressed the complete metabolic pathways for degrading 16 to 17 types of AAs in enrichments fed with respective substrates. These characteristics were distinct from cultured AA degraders including Acidaminobacter and Peptoclostridium, suggesting the uncultured Bacteroidales were the major protein-hydrolyzing and AA-degrading populations. These uncultured Bacteroidales were further found to be dominant and active in full-scale anaerobic digesters, indicating their important ecological roles in the native habitats. ‘Candidatus Aminobacteroidaceae’ was proposed to represent the previously uncharted family Bacteroidetes vadinHA17.